Perancangan User experience Sistem Informasi Evaluasi Kinerja Dosen Jurusan Sistem Informasi Fakultas Ilmu Komputer Universitas Brawijaya menggunakan Pendekatan Human Centered Design - Ria Nevita Rully Prastianila Indriani; Herman Tolle; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Lecturers' performance evaluation is a process where an institution carry out lecturers' performance evaluation using a certain criteria. Information Systems Department has utilized technology to support lecturer's performance evaluation. At the end of every semester lecturers would receive a report of lecturers' performance evaluation that can be downloaded from FILKOMAPPS. With various aspects to consider in a performance evaluation, user needs visualizations using dashboard to make data and information easier to understand. Based on said issue, a user experience dashboard design is made for Sistem Informasi Evaluasi Kinerja Dosen (SILUED) using the Human Centered Design Approach. With this design it is expected that management could monitor and evaluate lecturers' performance easily and also to make it easier for lecturers to access their performance result. In the usage context analysis stage, user identification, user characteristics, user's goal, system environment identification and persona are found. In the user requirement stage a summary of user interview is made into user requirements and content requirements. After usage context analysis and user requirement, the next step is designing the solution. From the result of the design solution there is 100% effectivity with 0.12 second for a user to finish one goal. The efficiency rate is 100% with SUS score of 78,75 where it can be categorized as acceptable with rating in ‘good' category.